1979
DOI: 10.1007/bf01408397
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear spectroscopy of neutron-richA=143 nuclei

Abstract: A study of the beta decay of 143Cs and ~'~3Ba fission products was undertaken by the use of two on-line mass-separators OSTIS and OSIRIS. Level schemes for 143Ba and 143La are deduced from gamma and conversion electron spectra, 7-7 and/%7 coincidences. Q~ values and ground state beta feedings were also measured. The nuclei l'~3La and 143Ba are tentatively inserted in a systematic of odd-even nuclei around A = 143 and even-odd nuclei with 87 neutrons respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
4

Year Published

1981
1981
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
1
6
0
4
Order By: Relevance
“…By far the strongest /%transition in the decay of ~43Cs is proposed by these authors to populate the ground state of the daughter nucleus; about 78 ~o of the total intensity is attributed to this /~-branch. The result of our measurements agree well with the relative /~-feedings given in [28] for the low-energy levels of l~3Ba. From the results of means of 7V-coincidence and w-angular correlation measurements.…”
Section: Rb6tsupporting
confidence: 89%
See 1 more Smart Citation
“…By far the strongest /%transition in the decay of ~43Cs is proposed by these authors to populate the ground state of the daughter nucleus; about 78 ~o of the total intensity is attributed to this /~-branch. The result of our measurements agree well with the relative /~-feedings given in [28] for the low-energy levels of l~3Ba. From the results of means of 7V-coincidence and w-angular correlation measurements.…”
Section: Rb6tsupporting
confidence: 89%
“…scheme has been studied in detail by Schussler et al [28], who found 56 v-transitions with energies between 34keV and 1,312keV, which depopulate 21 excited levels in t43Ba up to an energy of 1,453 keV. Very little, however, is known about the levels above this energy.…”
Section: Rb6tmentioning
confidence: 95%
“…Two low-excitation levels at 29.9 and 291.5 keV, along with three transitions of 29.9, 261.6, and 291.5 keV in Fig. 1 have been identified in the previous β-decay studies [15][16][17]. We add 20 new transitions and 13 new levels in the new scheme.…”
Section: Experiments and Resultsmentioning
confidence: 88%
“…In the previous β-decay experiments [15][16][17], many low-spin levels have been identified in 143 La, but no collective band has been reported. In this work, we report on identification of new collective bands with high-spin states and octupole correlations in 143 La.…”
Section: Introductionmentioning
confidence: 95%
“…[7,8]. From the various 6-endpoint energies, a consistent QB-value was obtained for each isotope studied in the present investigation.…”
Section: U Keyser Et Al: Very Neutron-rich Cs Isotopesmentioning
confidence: 99%